API480: features towards therapy in honeybee hives - Ribeiro, Henrique Gonçalves (2019)
American foulbrood disease (AFB) is a devastating bacterial disease affecting honeybees. It is caused by Paenibacillus larvae, a worldwide-distributed spore forming Gram-positive bacterium which spread easily across apiaries producing highly resistant spores. When AFB symptoms are found the burning of contaminated hives is mandatory causing serious economic losses [1]. Bacteriophages (phages) are being considered valuable solutions to the control of this infection [2-5]. So far, 48 Siphoviridae P. larvae phages sequences are known and most encode integration genes suggesting a temperate lifestyle. All of these 48 phages seem to have a common evolutionary ancestor showing an overall common structure. Their genomes were grouped into four clusters (with Fern, Harrison, Vegas and Halcyone as representative phages) and one singleton (phage Lily) [6].